Songbook : how lyrics became poetry in medieval Europe - Galvez, Marisa (University of Chicago Press, 2012)
'Songbook' treats what poetry was before the emergence of the modern category 'poetry': that is, how vernacular songbooks of the 13th to 15th centuries shaped our modern understanding of poetry by establishing expectations of what is a poem, what is a poet, and what is lyric poetry itself.